Activity Space and Accessibility: Characterizing Complex Urban Activity-Travel and Optimizing Service Provision Planning - Li, Ran (The University of Arizona., 2016)
Research on urban travel represents an important area in geography, transportation planning and urban studies. Compared to the traditional trip based approach, the activity based approach offers a better understanding of the motivations underlying travel, that is, activity participation. Urban activity-travel is complex as it takes place both in space and time. Building upon the time geography framework, this study provides new ways to characterize urban activity-travel and examine the association with accessibility. A new optimization model incorporating complex urban travel is also proposed for service provision planning. Activity space represents an important concept for understanding human activity-travel. The geometry based approaches widely used for delineating activity spaces are limited in fully characterizing real-world travel behavior. To address the issue, Chapter 2 proposes a new time geography based approach to more accurately portray urban activity spaces. The proposed approach takes into account the full complexity of real-world travel and underlying urban structures. Results of an empirical study are presented based on the 2008 Add-on National Household Travel Survey conducted in Tucson, Arizona. Activity spaces of 1,164 sample travelers are delineated and analyzed. Results show the effectiveness of the new approach in more realistically depicting urban activity-travel. Understanding the impact of the built environment on travel is important for formulating effective travel reduction policies. In Chapter 3, a study is presented to examine the relationship between accessibility to urban opportunities and urban travel. Activity spaces are drawn to characterize the spatial extent of activity-travel, and a new accessibility measure is introduced to account for the complexity of urban travel. An empirical study based on a travel survey dataset in Tucson, Arizona shows that improved accessibility is generally associated with reduced travel, but such an effect varies across different activity types. In addition, employment status and trip-chaining behavior can be used to explain the varying influences on the accessibility-travel relationship. In Chapter 4, a new multi-objective location model is developed with the goal of accessibility maximization. The model extends the classic p-median problem (PMP) to account for accessibility in a more realistic manner. Trip chaining and activity space are incorporated into the location model. In addition to fixed home locations, stops along chained trips are allowed for potential service site visits. The model is applied to locate service facilities in Tucson, AZ. Alternative versions of the objective function are solved exactly with the resulting sets of optimal facility locations displayed and analyzed. Decision makers are given flexibility to determine the relative importance for each of three sub-objective, based on the type of services being located, their preferences and practical needs.